"Ô de casa, ô de fora!" o reisado do mestre Marcolino em Morro de Chapéu e a memória subterrânea - Garcez, Fernanda da Silva (2024)
This work aims to analyze the "Reisado" of Mestre Marcolino in Morro de Chapéu, located in the Chapada Diamantina, and its role in the Subterranean Memory. It is a qualitative research, based on literature review and the analysis of photographs as methodological procedures. The images, considered visual sources and documents, enabled the understanding of the phenomenon of the Reisado of Senhor Marcolino, with an emphasis on the presence of black bodies, exploring the interaction of these elements in the construction of subterranean memory in the interior of Bahia. The study aims to comprehend the complexity of this memory, outlining a significant portrait of a cultural minority.